Amplitude analysis of the Bs0 → K∗0K[bar]∗0 decays and measurement of the branching fraction of the B0 → K∗0K[bar]∗0 decay - Aaij, Roel; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Comerma-Montells, Albert; D'Argent, Philippe; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2019)
The B0→K∗0K¯∗0$$ B^0→ K^{* 0}{\overline{K}}^{* 0} $$ and Bs0→K∗0K¯∗0$$ B_s^0→ K^{* 0}{\overline{K}}^{* 0} $$ decays are studied using proton-proton collision data corresponding to an integrated luminosity of 3 fb−1. An untagged and timeintegrated amplitude analysis of B(s)0 → (K+π−)(K−π+) decays in two-body invariant mass regions of 150 MeV/c2 around the K∗0 mass is performed. A stronger longitudinal polarisation fraction in the B0→K∗0K¯∗0$$ B^0→ K^{* 0}{\overline{K}}^{* 0} $$ decay, fL = 0.724 ± 0.051 (stat) ± 0.016 (syst), is observed as compared to fL = 0.240 ± 0.031 (stat) ± 0.025 (syst) in the Bs0→K∗0K¯∗0$$ B_s^0→ K^{* 0}{\overline{K}}^{* 0} $$ decay. The ratio of branching fractions of the two decays is measured and used to determine ℬB0→K∗0K¯∗0=8.0±0.9stat±0.4syst×10−7$$ \mathrm{\mathcal{B}}\left(B^0→ K^{* 0}{\overline{K}}^{* 0}\right)=\left(8.0± 0.9\left(stat\right)± 0.4\left(syst\right)\right)× {10}^{-7} $$.
Im Titel ist die "0" bei den Buchstaben B und K hochgestellt, "s" tiefgestellt und in Klammern
Im Titel ist beim ersten und dritten K "∗" hochgestellt
Im Titel ist das zweite und vierte "K" mit einem Oberstrich dargestellt, "∗" und "0" stehen rechts neben dem Oberstrich
The LHCb Collaboration: R. Aaij, S. Bachmann, D. Berninghoff, M. Borsato, S. Braun, A. Comerma-Montells, P. d’Argent, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, M. Heß, J. Hu, M. Kecke, M. Kolpin, R. Kopecna, B. Leverington, H. Malygina, J. Marks, D.S. Mitzel, S. Neubert, A. Piucci, M. Schmelling, N. Skidmore, M. Stahl, S. Stemmle, U. Uwer, R. Waldi, A. Zhelezov [und viele weitere]
Gesehen am 12.05.2020